(Invited) Polarization-Induced Doping in Graded AlGaN Epilayers Grown on AlN Single Crystal Substrates. (23rd July 2018) - Dalmau, Rafael; Moody, Baxter
Abstract : Compositionally graded Al x Ga1- x N epilayers were coherently grown on AlN single crystal substrates by MOCVD, and polarization-induced doping was determined by contactless sheet resistance and capacitance-voltage measurements on unintentionally doped, n-type graded layers; and by temperature-dependent Hall effect measurements on a Mg doped, p-type graded layer. The room-temperature resistivity, hole concentration, and hole mobility of the p-type layer graded from x = 1.0 to x = 0.36 were 1.2 Ωcm, 4.5x10 18 cm -3, and 1.2 cm 2 /Vs, respectively, which represents a significant improvement over traditional, thermally-activated Mg doping in AlGaN alloys.